Influence of Microwave Blanching on Arsenic Speciation and Bioaccessibility in Lentinus Edodes. (2nd September 2018) - Chen, Shuangyang; Xu, Jiajia; Chen, Guitang; Hu, Qiuhui; Zhao, Liyan
ABSTRACT: Humans are exposed to arsenic by inhalation and ingestion and are therefore may be affected by its toxicity. Arsenic may enter the human body by inhalation and ingestion. Cooking may alter the contents and chemical forms of arsenic. The determination of arsenic species in Lentinus edodes after microwave blanching was performed by high-performance liquid chromatography–inductively coupled plasma–mass spectrometry. Using a physiologically based extraction, the bioaccessibility of arsenic species in raw L. edodes and microwave blanching treated L. edodes were determined after the simulated gastrointestinal digestion. The arsenate (As V ), arsenite (As III ), monomethylarsonic acid (MMA), dimethylarsinic acid (DMA), arsenobetaine, and arsenocholine did not undergo decomposition and transformation in this study. Furthermore, the total contents of arsenic in L. edodes samples were in the range of 0.1378 ± 0.0044–0.2347 ± 0.0144 mg/kg. Approximately 3.38–43.27% were released from samples into the blanching water after various microwave blanching treatments. The oxidation of As III and demethylation of DMA and MMA were observed in L. edodes during digestion, increasing the likelihood of arsenic toxicity in the liver. The health risk for arsenic in L. edodes was decreased after microwave blanching because the potentially available arsenic in microwave blanching treatments L. edodes samples (83.78 ± 0.9103%) were lower than those in raw L. edodes samples (88.33 ± 0.7983%). L. edodes subjected to microwave blanching prior to consumption significantly decreased the total arsenic content and the risk of arsenic exposure to consumers ( p < 0.05).